2001
DOI: 10.1097/00004770-200104000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Trioxide Aggregate Repair of Lateral Root Perforations

Abstract: This study was conducted to observe the healing process of intentional lateral root perforation repaired with mineral trioxide aggregate (MTA). Forty-eight root canals of dogs' teeth were instrumented and filled. After partial removal of the filling, an intentional perforation was made with a bur in the lateral area of the root. The perforations were repaired with MTA or Sealapex (control group). Histological analysis occurred 30 and 180 days after treatment. Results showed no inflammation and deposition of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
0
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(184 citation statements)
references
References 18 publications
7
155
0
17
Order By: Relevance
“…[17][18][19] Hiremath and others 20 used calcium hydroxide and glass ionomer cement for the treatment of ICR and found that the tooth was without symptoms for only six months, but at the follow-up after six months, healing was incomplete. The use of MTA for treatment of ICR showed favorable healing compared with composite.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Hiremath and others 20 used calcium hydroxide and glass ionomer cement for the treatment of ICR and found that the tooth was without symptoms for only six months, but at the follow-up after six months, healing was incomplete. The use of MTA for treatment of ICR showed favorable healing compared with composite.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65][66][67][68][69][70] También, es usado como material de obturación apical. 63,[71][72][73] El MTA ofrece una barrera en la porción apical del conducto (tapón apical) en dientes con pulpas necróticas y ápices abiertos aplicable a casos donde la constricción apical no existe. 63 El pronóstico del trauma dental es incierto.…”
Section: Discussionunclassified
“…MTA 시멘트 는 치근 천공 6,7) , 분지부 천공 8) , 치근단 역충전 5,9) 등의 수복 재료로, 그리고 직접 치수 복조술 10,11) , 치근첨 형성술 12) 등의 술식에 널리 사용되고 있고, 생체친화도도 매우 우수한 재 료로 알려져 있다 13,14) . 그러나, MTA 시멘트의 이런 다양한 임상 적용과 장점에도 불구하고 3시간여에 이르는 긴 초기 경화 시간 15) , 이에 따른 initial looseness와 과도한 수분하 에서 재료의 washout, 조작의 어려움 등이 문제점으로 지 적된다 16) .…”
Section: ⅰ 서 론unclassified